Comparative International Accounting / Sixth Edition - Nobes Christopher; Parker Robert (Financial Times - Prentice Hall, 2000)
This successful text offers a comprehensive, yet coherent, examination of the international dimensions of financial accounting and reporting. Preface, Acknowledgements, Context of International Accounting, Introduction, Causes of International Differences, Major International Differences in Financial Reporting, International Classification of Financial Reporting, Harmonization and International Accounting Standards, Country Studies, Financial Reporting in the United Kingdom, Financial Reporting in the United States, Financial Reporting in the Netherlands, Financial Reporting in France, Financial Reporting in Germany, Financial Reporting in Japan, Financial Reporting in Nine Important Countries, Issues in International Accounting, Consolidation, Foreign Currency Translation, Segment Reporting, Inflation Accounting, Analysis and Management Issues, International Financial Analysis, International Auditing, Classification and Harmonization of Corporate Income Taxes, Managerial Accounting, References, Index.